Influence of temperature on the hydro-mechanical behavior of Boom Clay. (August 2018) - Yu, Hongdan; Chen, Weizhong; Gong, Zhe; Ma, Yongshang; Chen, Guangjing; Li, Xiangling
Abstract: The purpose of this study is to identify common properties, as well as specific features of Boom Clay with regard to its response to thermo-hydro-mechanical (THM) loading through laboratory experiments, particularly at temperatures significant for radioactive waste disposal. Triaxial shearing tests at various temperatures and various effective confining pressures were performed on Boom Clay samples under undrained conditions. Test results clearly show that under the same hydro-mechanical conditions, an increase in temperature can cause a decrease of shear strength of Boom Clay. This weakening in shear strength was further interpreted as the reduction in cohesion and elastic modulus, and also the pore pressure build-up due to temperature elevation. However, the temperature effect on the friction angle is not clear. The results obtained confirm the effect of the overconsolidation ratio (OCR) on the thermal volume changes (contraction or dilation). The laboratory test results presented here give additional information to gain more insight into the thermal influence of heat emitting wastes on the behavior of clay, to validate and calibrate models.